2020
DOI: 10.3389/fnins.2020.00230
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Adaptive Visuomotor Behavior Mediated by Non-linear Phase Coupling in Macaque Area MT

Abstract: The idea that a flexible behavior relies on synchronous neural activity within intra-and inter-associated cortical areas has been a matter of intense research in human and animal neuroscience. The neurophysiological mechanisms underlying this behavioral correlate of the synchronous activity are still unknown. It has been suggested that the strength of neural synchrony at the level of population is an important neural code to guide an efficient transformation of the sensory input into the behavioral action. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Generally, there are several measures to quantify the strength of QPC between all frequency pairs. For example, the TotalBic is the total bicoherence in the signal between specific frequency bands, which reflects the rhythmic synchronization between the oscillations in neuronal populations at different frequencies; the maximum eigenvalue and Shannon entropy of eigenvalues can be regarded as indices of global phase coupling for the whole bicoherence matrix, which measures the synchronization between oscillatory activities in the neuronal population; the DiagBic is a subset of the bicoherence values along the diagonal line of the bicoherence matrix, which reveals the self-frequency and self-phase coupling presented in neural circuits [34][35][36]. The Total-Bic was employed in this study because it performed better than the other indices in characterizing the orientation selectivity.…”
Section: Wavelet Bicoherence and Qpcmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, there are several measures to quantify the strength of QPC between all frequency pairs. For example, the TotalBic is the total bicoherence in the signal between specific frequency bands, which reflects the rhythmic synchronization between the oscillations in neuronal populations at different frequencies; the maximum eigenvalue and Shannon entropy of eigenvalues can be regarded as indices of global phase coupling for the whole bicoherence matrix, which measures the synchronization between oscillatory activities in the neuronal population; the DiagBic is a subset of the bicoherence values along the diagonal line of the bicoherence matrix, which reveals the self-frequency and self-phase coupling presented in neural circuits [34][35][36]. The Total-Bic was employed in this study because it performed better than the other indices in characterizing the orientation selectivity.…”
Section: Wavelet Bicoherence and Qpcmentioning
confidence: 99%
“…Specifically, the gamma-band LFPs play a critical role in the visual information processing. For example, the higher gamma rhythms are mostly linked to the fastspiking visual neurons [22]; the orientation selectivity in V1 of awake monkey is modulated by gammaband LFPs [23]; the distinct bands (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) Hz for low gamma and 60-80 Hz for high gamma) of stimulustriggered gamma oscillations are systematically linked to the orientation selectivity index of neurons in the cat primary visual cortex [24]. Therefore, studying the gamma-band LFPs is of great significance to understand the mechanism for generating the orientation selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies have shown complex brain information interaction between different frequency bands, known as cross-frequency coupling (CFC). Several brain regions of human and non-human primates found CFC phenomena, such as the hippocampus, prefrontal cortex, and sensory cortex (Mormann et al, 2005 ; Canolty et al, 2006 ; Jensen and Colgin, 2007 ; Khamechian and Daliri, 2020 ). Besides, increasing researchers use CFC to analyze cognitive and perceptual processes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the three properties of a signal, i.e., frequency, amplitude, and phase, there are four fundamental types of CFC, including phase–frequency coupling (PFC) (Roberts et al, 2013 ), phase–phase coupling (PPC) (Belluscio et al, 2012 ), phase–amplitude coupling (PAC) (Tort et al, 2010 ), and amplitude–amplitude coupling (AAC) (Yeh et al, 2016 ). PAC reflects the degree that the amplitude of higher-frequency oscillations is modulated by the phase of lower-frequency oscillations (Canolty et al, 2006 ), which is the most common and important type of CFC and plays a major role in the brain functions such as motion (Cheung et al, 2019 ; Khamechian and Daliri, 2020 ), memory (Tseng et al, 2019 ), learning (Zaleshin and Merzhanova, 2019 ), and sleep (Cox et al, 2019 ). There are many algorithms to estimate PAC, such as mean vector length (MVL) (Canolty et al, 2006 ), modulation index (MI) (Tort et al, 2008 ), and generalized eigendecomposition-based cross-frequency coupling framework (gedCFC) (Cohen, 2017 ).…”
Section: Introductionmentioning
confidence: 99%